Fluorescence Assays to Study Membrane Penetration of Proteins - Senju, Yosuke; Zhao, Hongxia (Methods in molecular biology (Clifton, N.J.), 2021)
Phosphoinositides play important roles in the regulation of protein recruitment at specialized membrane domains, protein activity, and membrane dynamics. Phosphoinositide-protein interplay occurs via multiple mechanisms and proteins associate with membranes through different binding patterns. Determinations of membrane-binding mode and membrane penetration depth of proteins in lipid bilayer are thus important steps in characterizing the molecular mechanisms of membrane-protein interactions. Here, we show two standard in vitro assays using liposomes, diphenylhexatriene (DPH) anisotropy, and fluorescence quenching by brominated lipids to determine membrane penetration of proteins into lipid bilayer. These methods will provide useful tools to study membrane-protein association and uncover molecular details of protein-lipid interplay, which are important for understanding biological functions of membrane-associated proteins and membrane dynamics.